Pengaruh Kewirausahaan Batik Jambi Terhadap Perekonomian Keluarga Di Kelurahan Jelmu Kecamatan Pelayangan Kota Jambi - Alatas, Sundari Iza; Kasiono, Kasiono (SJEE (Scientific Journals of Economic Education), 2024)
This research aims to determine the influence of Jambi Batik in improving the family economy in Jelmu Village, Pelayangan District, Jambi City. This type of research uses quantitative research methods with a descriptive analysis approach. The research results show the influence of Jambi Batik entrepreneurship in improving the family economy in Jelmu Village by improving production, distribution, marketing and marketing techniques, in the sufficient category.